Implementasi Mailtrack Pada Surat Menyurat di Bagian Perencanaan dan Keuangan Sekretariat Daerah Kabupaten Malang - Hilda Nihayatul Aulya; Fitria Erika Sari; Yenie Eva Damayanti (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2023)
This service focuses on the implementation of mailtrack on correspondence in the planning and finance section of the Malang district secretariat. The purpose of this service is to find out the mailtrack on correspondence in the planning and finance department at the Malang district secretariat. In this service using descriptive qualitative research methods. The object of this research uses secondary data data derived from literature studies, such as books, journals, articles, and so on. Data collection techniques are literature studies, documentation. The results of the study show: 1) Management and explanation of incoming and outgoing mail, and office filing in the planning and finance department 2) Electronic-based management (incoming mail) (Mailtrack), steps for electronic-based incoming mail (Mailtrack). Receiving letters (e-mail), sorting letters, recording letters, storing letters Keywords: Incoming mail, Outgoing mail, Filing, Mailtrack